PENDAMPINGAN MASYARAKAT KELURAHAN PARIT LALANG DALAM DIGITALISASI DAN SPASIALISASI WILAYAH - Hidayah, Ulul; Amo, Farisa Maulinam; Dewi, Refika; Agita, Meri; Saputra, Yuda; Lestari, Julia (LPPM Universitas Nusa Mandiri, 2025)
Spatial planning requires diverse, comprehensive, accurate, and detailed data to forecast spatial development needs. Parit Lalang Subdistrict is located in Rangkui District, Pangkal Pinang City. The potential of Parit Lalang Subdistrict has yet to be identified well enough and accurately. Community assistance aims to digitize and spatialize the potential of Parit Lalang Village. This community program is carried out in three stages: preparation, implementation, and evaluation. The team carried out coordination activities and prepared training modules in the preparation stage. Participatory mapping activities (spatialization) and spatial data digitization training were carried out at the implementation stage. At the evaluation stage, evaluation meetings are carried out, and the results of the activities are submitted to partners. This community assistance activity results in data on potential and neighborhood problems that can be mapped and published digitally as a database for preparing planning programs. The database is arranged in map form, including regional boundary maps, land use maps, and supporting infrastructure maps. From this mentoring activity, a digitalization and spatialization module was also produced, a guidebook that can be used by village governments if they want to map regional potential. The enthusiasm of the people and government of Parit Lalang Subdistrict is quite high in identifying the area's potential so that similar activities can be replicated in other villages. The availability of digital spatial data formats can increase the reach of public information on the potential and conditions of residential areas, thereby providing efficiency in meeting community needs from a development aspect.